Pengembangan Multimedia Pembelajaran Interaktif Berbasis Video Untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Munawaroh, Munawaroh; Sudrajat, Sanin; Saepudin, Saepudin; Rinjani, Novinda; Hasanah, Uswatun (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Students' interest in learning increases students' enthusiasm and activeness in the learning process. However, in the field, learning to be a student is quite challenging. The aim of this research is to improve video-based interactive multimedia learning to improve student experiences in elementary schools. The research method used is R & D, with the aim of creating video-based interactive multimedia for elementary school students and determining the quality of interactive multimedia based on media, material and technical requirements. Based on the research results, the media has a score of 82.9% in the good category and 89.5% in the very good category. Choosing small groups has an 82% chance of success, while choosing large groups has an 80% chance of success. The teacher evaluation results have a chance of success of 92.6%. The chance of success is 82%, while choosing a large group has an 80% chance of success. Learning research finds that students learn better with tests, with scores found to be 0.61 for satisfaction and 0.69 for interest.  Furthermore, exams improve all aspects of student learning by 0.64, especially in the current category. As a result, creating video-based interactive multimedia can improve students' learning experiences